Market Integration and Seasonal Price Variation of High-Value Vegetable Crops in Chittagong Hill Districts of Bangladesh - Rayhan, Shah Johir; Islam, Md Jahurul; Kazal, Mohammad Mizanul Haque; Kamruzzaman, M (International Journal of Sustainable Agricultural Research, 2019)
The present study analyzed the spatial price integration and seasonal price variations of brinjal and yard-long bean in the Chittagong hill districts of Bangladesh. Secondary data were amassed from the Department of Agricultural Marketing (DAM) for the time period of 2006-2015. Correlation coefficient and Engle-Granger (EG) co-integration tests were used as a tool for analyzing price integration among selected district markets. For the estimation of seasonal price variation, ratio to moving average method was adopted for the study. The findings of the study from this observed evaluation of spatial price linkage through correlation coefficients and co-integration among the selected markets of Bangladesh considering the wholesale price of selected vegetables indicated that these markets were well integrated but not strongly integrated. That means the Chittagong market for each commodity was significantly integrated but not significantly highly integrated because of not as much developed transportation system in the hilly areas. The average seasonal variation of price of brinjal was found to be the maximum in the month of October and the minimum in the month of March. The average seasonal price variation of yard long bean was utmost in February and lowest in the month of June. The outcome of the present study could benefit the farmers and market actors monetarily if the production and marketing system of vegetables are well developed.